A Method to Shorten Signals in SM-OFDM - Lizarraga, Enrique M. (2017)
Spatial modulation (SM) added to traditional OFDM communications has been intensively studied as a candidate transmission method to convey high-speed, low-delay, powerefficient and high-mobility 5G communications in a reliable basis. This approach implies the use of multiple antennas at the transmitter. Then, the fundamental aspect revised in this work takes into account that in a single-carrier SM system, the selection of the active transmit antenna according to (part of) the information bits makes it possible to use a single power amplifier (PA) that is switched among the available antennas. On the other hand, in a conventional SM-OFDM system, every antenna needs to be continuously active as the index information is typically different for each subcarrier. Consequently, we propose a transmission scheme that precodes the information symbols in frequency domain, such that the global symbol period is split into partitions that enable a sequential operation of antennas which can be fed by a single PA. In addition, it is possible to establish that the proposed approach tends to be more robust against disturbances observed in high mobility environments.